Clubroot on Oilseed Rape/Canola: A Review (Journal of Oilseed Brassica, 2026)
Plasmodiophora brassicae causes the disease clubroot in cruciferous plants, and has been a threat to brassica crops production all over the world since its identification. Clubroot has become a major economically important disease of oilseed rape (OSR) in many countries, especially in areas where cool, cloudy, and humid weather persists. Further, the importance of the disease can be determined by its spread in about 88 countries globally on >3700 species of plants, with > 60 vernacular names accountable for 10-100 per cent losses to brassica vegetables, and oil yielding crops. The pathogen P. brassicae survives in soil as the long time survival structures commonly known as resting spores, and are viable up to 17 years. The resting spores of P. brassicae are highly robust and are well protected by five spore walls. These spore walls are composed of fungal chitin, and carbohydrates that makes the spores resilient to degradation by extra-cellular enzymes produced by predatory soil organisms. Root galls are the characteristics symptoms of the disease clubroot, which function as strong metabolic sinks in infected plants by drawing nutrients, and other resources away from the shoots, and leaves contributing to above ground symptoms development. There have been extensive investigations on pathological, physiological, and molecular characteristics of P. brassicae causing clubroot on OSR/ canola and over 300 brassica hosts that gives the researchers a scope to work on this pathogen and its management across the world. In management of the disease clubroot lack of chemical control option coupled with the need for longer crop rotations forced the deployment of host plant resistance as a major option for clubroot management. Effective and repeatable controlled-environment and field-screening techniques have been developed for identification of host plant resistance. P. brassicae genome is small in size (24.2-25.5 Mb) with high gene density. The pathogen contains genes potentially involved in host hormone metabolism and metabolic pathways. Mapping of quantitative and qualitative traits loci (QTL’s) have revealed several (12) dominant loci in B. rapa over 22 QTL’s in B. oleracea and more than 19 QTL’s in B. napus for clubroot resistance to different pathotypes of P. brassicae. Eventually several genes governing quantitative and qualitative resistance to P. brassicae have been identified and characterized in different Brassica species. However, some of genes have been demonstrated to be related to the pathogenicity of P. brassicae. Extensive use of the resistant cultivars in shorter crop rotations has resulted in emergence of the pathotypes in OSR/canola. The pathotypes of P. brassicae display great variations with tendencies for overcoming resistance sources from Brassica species in a short period of time. Soil amendments with different types of lime based on pH of the soil were helpful in small scale applications or in patches. However, the interactions of physical, chemical, and biological, properties between P. brassicae, and Brassica hosts and non-hosts in the soil environment are very complex, and pose challenges to determine conduciveness and suppressiveness of the disease or the pathogen. Integrated disease management (IDM) of clubroot has proved more effective than any of the individual disease management components in large-scale and in on-farm studies conducted in Canada and in the USA. Further information on the biology of P. brassicae and epidemiology of the disease is needed to strengthen the IDM programs. Current manuscript summarizes on recent studies into the; geographic distribution, morphology, molecular biology, taxonomy, life cycle, symptoms, ecology, host range, genetic basis of resistance, pathotypes, soil pH, quantification of resting spores from soil and available management practices of clubroot on OSR/canola have been reviewed with a mention of future research priorities.